First case report of Candida guilliermondii native left-sided valve endocarditis - Zheng, Zilong; Tu, Xiaokang; Jiang, Chuanhao; Liu, Feng; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2023)
Endocarditis, a life-threatening inflammation of the endocardium, is incited by bacteria, fungi, or other pathogenic microorganisms. Fungal endocarditis closely mirrors bacterial endocarditis in clinical signs and symptoms, leading to potential misdiagnoses. Here, we unveil the inaugural confirmed instance of native left-sided valve endocarditis attributed to Candida guilliermondii. Diagnosis was substantiated through valvular biopsies, blood and vegetative cultures. Treatment encompassed surgical excision of vegetations along with a six-week regimen of fluconazole administration (12mg/kg/day), followed by four years of meticulous monitoring, resulting in sustained patient recovery.